Investigating of mechanical properties of reinforced plastics (fiberglass) - Mohd Aiman, Md Johari (2008)
Fiberglass is refers to a group of products made from individual glass fibers combined into a variety of forms and act as reinforcing agent. The objectives of this project are to study on mechanical properties of fiberglass, investigate the relation between fiberglass and polyester resin, and to understand on the mechanical behaviour of fiberglass. The problem of bonding between fiber and the matrix resin affect the strength of the fiberglas and this need to be deals with the study on their mechanical properties by using mechanical experiment test. Test test is carried out using Tensile Test, Izod Test, and Charpy Test, which all are focusing on investigating mechanical properties on the specimens. Fiberglass is made up by using hand lay-up technique, where different laminate of fibreglass made up by different mass of resin which result difference thickness. The aim of the test is to study on this fibreglass strength, impact strength, and to observed on the mechanical behaviour of this material. It was found that the higher the thickness of fibreglass, the stronger the fibreglass be.